Are the Rumours True that COVID was Spread by Pilgrims/Travellers Coming to Baluchistan from the Pakistan Iran Boarder? A Multidistrict Case Representation Study - Bugti, Muhammad Anwar; Baloch, Yasir; Shaikh, Zeeshan; Zarak, Muhammad Samsoor; Ahmed, Mansoor; Khan, Najeebullah (Infectious Diseases Journal of Pakistan, 2022)
Background: Almost 8000 pilgrims had returned to Pakistan at that time but before the government could set up a quarantine centre, the secondary cases started occurring in the country. Among all these reported cases, 60% were those people who travelled to Iran. The study aimed to assess the demographics of the spread of coronavirus in Baluchistan while also showing the rate of initial transmission of the virus from the Pakistan-Iran border also known as the Taftan Border. Methods: This is a descriptive cross-sectional study from the very first COVID-19 positive tested case i.e. Mar 2019 up till 19th April 2020. Total 5315 COVID-19 tests were conducted, out of which 432 were found to be positive and screened for this study material. Result: A total of 5315 tests were conducted and out of them, 432 were positive, and 4883 were negative. The results showed that 328 cases (75.9%) were from the Quetta district. Quetta and Loralai have displayed the highest COVID-19 attack rate among 14 of all the other districts. The first timeline for the spread of covid- 19 was high as the religious pilgrims and other international travelers were entering the country till mid-March. Conclusion: A significant contribution of this study provides the first account of the COVID-19 epidemic curves of Pakistan. However, this is the first report from Baluchistan, and it may be difficult to predict the course of this virus and its impact in the coming future. Keywords: COVID-19, Attack Rate, Route of Spread, International Travelers, Baluchistan-Pakistan